"Pressure pain threshold over masticatory muscles and temporomandibular joint in patients with juvenile idiopathic arthritis". (28th June 2020) - Valentino, Roberta; Rongo, Roberto; Alessio, Maria; Alstergren, Per; Bucci, Rosaria; Leone, Giovanna; D'Antò, Vincenzo; Michelotti, Ambrosina
Abstract: Background: Juvenile idiopathic arthritis (JIA) is an autoimmune, chronic, inflammatory joint disease, affecting children and adolescents. Patients with JIA may have pain and fatigue in muscles. There are not studies evaluating the pressure pain thresholds (PPTs) of both masticatory muscles and temporomandibular joint (TMJ) in patients with JIA. Objective: This study aimed to investigate PPTs of masticatory muscles and TMJ in subjects with JIA. Methods: Fifty‐one JIA patients and fifty‐two healthy subjects were recruited. JIA group was assessed for with a standardised clinical examination for temporomandibular disorders. In all subjects, the PPT was evaluated in the following sites: anterior temporalis (AT) and masseter (MM) muscles, TMJ and thenar (TH) eminence. Comparisons between groups were assessed with unpaired t test and ANOVA ( P < .05). Results: Pressure pain thresholds were significantly lower among JIA patients compared with controls ( P < .001) for all analysed sites. The presence of TMJ pain at palpation was significantly associated with a lower PPT at TMJ ( P = .031). Conclusions: Patients with JIA have generally lowered pain threshold to mechanical stimulus, which suggests an effect of JIA on nocicepton‐modulating processes.